HASIL BELAJAR OTONOMI DAERAH MELALUI METODE KONTEKSTUAL (CTL) BAGI SISWA KELAS IX-B SMPN 5 KERINCI - Sriati Sriati (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2018)
This research starts from the low student learning outcomes which is reflected in the value of 52.38% the average daily students are below the minimum completeness of learning that is 70. The purpose of this study is to improve student learning outcomes in the material of Regional Autonomy through the application of Contextual Teaching and Learning for students of class IX-B in semester I of Junior High School 5 Kerinci academic year 2017/2018. Subjects in this study were students of class IX-B Kerinci Senior High School 5 Kerinci Regency with a total of 21 students, 5 male students and 16 female students. This research was carried out in two cycles, where each cycle was held two meetings with 4 stages of planning, implementation, observation, and reflection analysis. Data analysis techniques in PTK are descriptive analytical. The results of classroom action research using a two-cycle pattern, apparently can test the action hypothesis proposed in this study. The results are; the results of the learning evaluation in the first cycle which only reached an average score of 72.47 increased in the second cycle which reached 75.86. In the second cycle students have achieved the expected mastery of learning that is 90.48% compared to the first cycle which is only 66.67%. This means that at the end of the second cycle all target criteria can be met, therefore the submitted can be accepted.